2020
DOI: 10.3390/nano10020213
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Reuse of Magnetic Black Carbon Magnetite (BC-Mag) for Fast Carbamazepine Removal from Water

Abstract: Magnetic carbonaceous nanomaterials are needed in water treatment applications because they can offer both carbon surfaces for sorption of organic pollutants and ease of material magnetic retrieval for regeneration and reuse. In this study, we employed a facile one-step method to synthesize a black carbon-magnetite composite (BC-Mag) by high-temperature annealing of black carbon and hematite. The nanocomposite was easily dispersed and stable in water owing to the presence of negatively charged oxygen surface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In order to create more efficient lithium (Li-ion) cells, Martínez-Rodríguez et al [15] used a biomineralization approach based on the effective framework of silk proteins to create hierarchical olive-like organized magnetite and carbon nanomaterials. Cai and Larese-Casanova [16] also showed that they could use this method to make electrocatalyst for high-performance Li-ion batteries. Rape pollen protein was used to facilitate and control the development of hierarchical meso/macroporous TiO2 systems in three dimensions.…”
Section: Peptide Monomersmentioning
confidence: 98%
“…In order to create more efficient lithium (Li-ion) cells, Martínez-Rodríguez et al [15] used a biomineralization approach based on the effective framework of silk proteins to create hierarchical olive-like organized magnetite and carbon nanomaterials. Cai and Larese-Casanova [16] also showed that they could use this method to make electrocatalyst for high-performance Li-ion batteries. Rape pollen protein was used to facilitate and control the development of hierarchical meso/macroporous TiO2 systems in three dimensions.…”
Section: Peptide Monomersmentioning
confidence: 98%